Output pulse energy from pulsed single-mode fiber amplifiers - Bingham, Samuel P.; Matyas, Daniel; Mihalik, Mark; Hawkins, Thomas W.; Kalichevsky-Dong, Monica T.; Ballato, John; Dong, Liang (Frontiers in Physics, 2025)
There is a lack of general study of the maximum pulse energy from fiber amplifiers with short durations (up to few hundreds of nanoseconds) that are limited by amplified spontaneous emission, which slows inversion growth and degrades pulse contrast. We have conducted a systematic study of a monolithic master oscillator power amplifier (MOPA) by varying pulse duration, repetition rate and fiber length using an in-house fabricated ytterbium-doped double-clad 50/250 fiber that demonstrated ∼20ns pulses at ∼1.5 mJ, 100 kHz repetition rate and ∼200 W average power with an M2 = ∼1.1. The highest pulse energy obtained is ∼1.7 mJ within the main pulse. This pulsed fiber laser was limited only by fiber fuse, which happens roughly between 1 and 2 mJ pulse energy regardless of pulse durations, fiber lengths and repetition rates tested. The model reported herein in this study is consistent with most experimental data in the literature and our own experimental data.